A study on green technology efficiency of China’s marine ship industry chain based on meta-frontier framework and three-stage EBM model - Guan, Hongjun; Wang, Yu; Zhao, Aiwu (Frontiers in Marine Science, 2022)
Based on the micro-data of 79 listed companies in the Chinese marine ship industry chain from 2015 to 2019, this paper calculates the comprehensive technical efficiency (TE), pure technical efficiency (PTE), and scale efficiency (SE) of the upstream, midstream, and downstream of China's marine ship industry chain with the three-stage super-efficiency slacks-based model (SBM), further analyzes the short board of industrial chain efficiency and its influencing factors. It is found that: (1) the TE and PTE of the upstream, midstream, and downstream of China’s marine ship industry chain are in a “V”-shaped distribution with high at both ends and low in the middle, but the SE is upstream > midstream > downstream. Besides, the PTE is the main reason that hinders the improvement of TE in the industrial chain. (2) The environmental variables have significant impacts on the industrial chain efficiency. After excluding the influences of environmental variables and random error terms, the industrial chain efficiency has changed significantly. The value of SE and TE has decreased significantly, and the distribution characteristic of TE has changed. But the PTE is still in a “V”-shaped distribution, and has become the main driving force for the progress of TE. (3) China’s marine ship industry chain has obvious efficiency short boards, and the midstream and downstream need to focus on development. Each link of the industry chain has high coupling and low coordination, all of them are closely related to each other, but the coordination ability is insufficient. There is still a large space for the improvement of the industrial chain in terms of efficiency and coordinated development.